(untitled) (International Conference on Computers in Education, 2020)
In recent years, e-books have been spotted in language learning research. A literature review is adopted to detect some gaps in specific areas in this study. Specifically, this paper reviewed the language learning with e-books studies published from 2010 to 2019 in selected journals from the Web of Science to explore the features and trends. A total of 43 selected studies were manually and systematically analyzed, revealing the following outcomes. The results indicated that 1) the most common participants are from preschools and elementary schools, but rarely from the secondary education level. 2) Preparatory e-books are the most commonly used. 3) Guided learning is most often adopted with e-books. 4) Reading is the primary target skill. 5) Nearly a half of the research results were positive, and nearly half were mixed. In order to support pedagogical practice with e-books, analyzing the effectiveness of functions or systems embedded in e-books would be necessary. More findings are provided to examine the usability and functionality of systems or functions in e-books and to assist teacher instructional guidance.